Zal ozhidaniia. Uroki leninizma na Leningradskom vokzale . Zal ozhidaniia. Uroki leninizma na Leningradskom vokzale . The Waiting Room. Lessons of Leninism at the Leningrad Station . Зал ожидания. Уроки ленинизма на Ленинградском вокзале - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. The program debates the significance of Leninism and its impact on the current political situation in Russia. Featured in the program: Novodvorskaia, Valeriia Il'inichna (Human Rights Activist); Umalatova, Sazhi (Politician); Nikiforov, Lev (Doctor of Economic Sciences) Contributors: Radov, Aleksandr (Anchor) Дискуссия о значении ленинизма и его влиянии на нынешнюю политическую ситуации в России. В программе участвуют: Новодворская, Валерия Ильинична (Правозащитница); Умалатова, Сажи (Политик); Никифоров, Лев (Доктор экономических наук) Создатели: Радов, Александр (Ведущий/Ведущая)